Sustainable technology for the production of artisanal cassava starch - Rodríguez Salazar, Arsenio José (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Yucca starch (Manihot esculenta Crantz) plays several important roles in agroecological agriculture in the tropics. It is an inexpensive source of carbohydrates of high nutritional quality and easily accessible, if preserved and stored. The process of starch artisanal extraction is carried out in Latin America in a rudimentary and impractical way, with water and raw material wasted, which generates losses and ecological problems. This study shows how a prototype of a technological process (Matilda v1.0) for the artisan extraction of yucca starch was designed, built, and optimized. The optimization was performed using the response surface methodology, and the experimental design is a Box-Wilson 23 full factorial central composite, uniformly rotated and orthogonally blocked per day. Around 60 kg of starch for 200 kg yucca on a working day was obtained. The estimated starch yield was 31.83%, within a confidence interval of (30.24-32.97%) and a prediction interval of (27.98-35.23%). This yield was higher than that reported for conventional artisanal extraction. Water use was about 0.3 L kg-1 yucca, significantly lower than in artisanal productions. The process developed would generate a lower impact on the environment and would allow small producers to empower themselves with sustainable technologies.